Effect of Reciprocal Learning in Big Ball Games to Improve Physical Literacy of 12-Year-Old Junior High School Students - Sugiarto, Tatok; Darmawan, Arief; Novita Sari, Zihan; Priyohutomo, Ahadi; Putri Hariyoko, Vania (Universitas Suryakancana, 2024)
Physical literacy is the development of various human movements consisting of basic movement skills and basic sports skills, so that these skills provide tools for humans to do physical activities that improve or maintain lifelong health. On average, students after school do not have time to do physical activities, this shows that awareness of physical activity is very low, in addition, in physical education learning there are still students who lack and have not optimized physical activity, so that motivation, understanding, knowledge and movement activities in children decrease. This study aims to determine the effect of reciprocal learning in big ball games in improving physical literacy in 12-year-old children at the junior high school level. The method in this study uses a randomized control group pretest-posttest design experimental study, this experimental study was conducted on a group with a control or comparison group, the research sample consisted of 12-year-old children at the junior high school level, the research instrument used in this study adopted from the measurement of physical literacy from the Canadian Assessment of Physical Literacy (CAPL). The results in the independent t-test output table in the equal variances assumed section are known to have a Sig (2-tailed) of 0.015 <0.05 so that a decision can be taken that in the independent sample t-test it can be concluded that Ho is rejected and Ha is accepted, thus the results of this study conclude that there is a significant difference in the final test results of reciprocal learning in big ball games in improving physical literacy between the intervention group and the control group.